Sleeve Gastrectomy Reduces Glycemia but Does Not Affect Cognitive Impairment in Lean 5xFAD Mice - Samuel, Itia; Ben-Haroush Schyr, Rachel; Arad, Yhara; Attali, Tamar; Azulai, Shira; Bergel, Michael; Halfon, Aviv; Hefetz, Liron; Hirsch, Tamir; Israeli, Hadar; Lax, Neta; Nitzan, Keren; et al. (Frontiers in Neuroscience, 2022)
Obesity and hyperglycemia are risk factors for cognitive decline and for the development of Alzheimer’s Disease (AD). Bariatric surgery is an effective treatment for obesity that was shown to improve cognitive decline in obese patients. Bariatric surgery was shown to exert weight loss independent effects on metabolic diseases such as type 2 diabetes. We tested whether sleeve gastrectomy (SG), a common bariatric surgery, can affect the cognitive impairment in lean, normoglycemic female 5xFAD mice, a genetic model for AD. 5xFAD mice and wild-type (WT) littermates underwent SG or sham surgery at the age of 5 months and were tested for metabolic, behavioral, and molecular phenotypes 90 days later. SG led to a reduction in blood glucose levels and total plasma cholesterol levels in 5xFAD mice without inducing weight loss. However, the surgery did not affect the outcomes of long-term spatial memory tests in these mice. Analysis of β-Amyloid plaques corroborated the behavioral studies in showing no effect of surgery on the molecular phenotype of 5xFAD mice. In conclusion, SG leads to an improved metabolic profile in lean female 5xFAD mice without inducing weight loss but does not affect the brain pathology or behavioral phenotype. Our results suggest that the positive effects of bariatric surgery on cognitive decline in obese patients are likely attributed to weight loss and improvement in obesity sequelae, and not to weight loss independent effects of surgery.